HUBUNGAN FREKUENSI, PORSI DAN JENIS MAKAN DENGAN GASTRITIS MAHASISWA KEDOKTERAN UNIVERSITAS BAITURRAHMAH PADANG ANGKATAN 2019 - Aryaldy Zulkarnaini; Vina Tri Septiana; Rosmawaty, Rosmawaty; Shinta Brisma; Fadhlurrahman, Fadhlurrahman (Yayasan Nusantara Hasana Berdikari, 2023)
Gastritis is a condition in which the lining of the stomach, or inflamed gastric mucosa. The lining of the stomach contains parietal cells which produce acids, enzymes, and mucus. Acids and enzymes break down food and aid digestion and mucus protects the mucosa from being damaged by stomach acid. Characteristics of gastric inflammation include anorexia, a feeling of fullness or discomfort in the epigastrium, nausea, and vomiting. This study aims to determine the relationship between diet and gastritis incidence in students at the Faculty of Medicine, Baiturrahmah University class of 2019. This study used an observational analytical method with a cross sectional design using primary data with a total sample of 115 respondents. Univariate data analysis is presented in the form of frequency distribution and bivariate analysis using chi-square test. Based on the results of this study, 75 (65,2%) had positive gastritis, and as many as 59 (51,3%) had a poor diet. The results of statitical tests showed taht there was a relationship of diet ti incidence of gastritis (p=0,003). This study has a meaningful relationship between diet and gastritis in students at the Faculty of Medicine, Baiturrahmah University class of 2019.